Elections and "sons of the soil" conflict dynamics in Africa and Asia. Issue 4 (6th June 2016) - Côté, Isabelle; Mitchell, Matthew I.
Abstract : Recent research reveals that nearly one-third of ethnic civil wars since 1945 have been "sons of the soil" (SoS) conflicts that pit indigenous populations against internal migrants. Despite important differences across SoS conflicts, many share a common trait as they often escalate during elections. While scholars have examined the causal mechanisms behind electoral violence, the relationship between elections and SoS conflicts has been overlooked. By examining a wide range of cases, the article breaks with previous research that privileges in-depth case studies of SoS conflicts with high levels of violence. Using insights from recent fieldwork in Côte d'Ivoire, Ghana, and Indonesia, the article sheds light on the causal dynamics that link elections and diverging levels of SoS conflict. In so doing, it illustrates how the severing of patronage networks and the shifting balance of power towards migrants create fertile contexts for political elites to instrumentalize local grievances. Elections are thus more likely to produce violent SoS conflicts when elites (at both the national and local levels) are able to mobilize supporters by playing upon these grievances, often through the politicization of citizenship and/or the ethnicization of the local sphere.